The willingness to pay for beach recreational facilities in Malaysia - W Mohamad, Wan Norhidayah; Abdul Fataha, Faten Nabila; Samdin, Zaiton; Basri, Bakti Hasan (Universiti Putra Malaysia, 2022)
The tourism sector plays an important part in Malaysia's economy. It includes beach and recreational tourism. However, most recreational beaches in Malaysia do not impose an entrance fee on visitors. Depending on government funding to maintain recreational beach facilities is not the best option for the future. Therefore, funding directly from visitors is needed to help cater for beach maintenance costs. Based on this, it is crucial to understand how much visitors are willing to pay for the recreational use of beaches, as any money collected could be used to help to improve facilities and services at beach areas. This study investigated visitors' willingness to pay for recreational beach facilities and has provided policy recommendations for better management of tourist facilities and services in the future. Teluk Kemang beach in Port Dickson was chosen as the case study location. This study applied the Choice Experiments (CE) method, and the model used was the Conditional Logit (CL) model. This research used four attributes: amenities, recreational facilities, cleanliness, and entrance fee. The CL results revealed that visitors were willing to pay for good amenities and cleanliness, with values of RM2.07 and RM2.43, respectively. Therefore, it was discovered that it was practical to charge an entrance fee to cover improved maintenance of beach facilities.